Single-cell RNA sequencing identifies macrophage transcriptional heterogeneities in granulomatous diseases. Issue 6 (17th June 2021) - Liao, Shu-Yi; Atif, Shaikh M.; Mould, Kara; Konigsberg, Iain R.; Fu, Rui; Davidson, Elizabeth; Li, Li; Fontenot, Andrew P.; Maier, Lisa A.; Yang, Ivana V.
Both sarcoidosis and chronic beryllium disease (CBD) are granulomatous diseases with overlapping clinical features; however, their clinical courses differ. CBD may have slow clinical progression and rarely resolves, while sarcoidosis has variable progression and may resolve depending on the stage of the disease [1]. These commonalities and differences imply differences in antigen(s), and potentially clearance and persistence. Alveolar macrophages play an important role in this process, driving innate [2] and adaptive immune responses [3]. Furthermore, subpopulations of macrophages may promote granulomatous inflammation and resolution of lung injury [4], key aspects of sarcoidosis and CBD. Using single-cell RNA sequencing (scRNA-seq), we explored the common and unique pathways between progressive (SarcP) and remitting (SarcR) sarcoidosis as well as CBD and sarcoidosis, focusing on macrophages and macrophage subpopulations (recruited versus resident). scRNA-seq characterised macrophage transcriptional and chromatin accessibility profiles in BAL cells in granulomatous lung diseases, chronic beryllium disease and sarcoidosis, and identified signatures of disease progression in sarcoidosis. https://bit.ly/3piFIBy